Household Factors Associated with Underweight in Children 24-59 Month in Urban and Rural in Indonesia - Yunitasari, Andini Retno; Dewi Sartika, Ratu Ayu; Setiarini, Asih (Media Kesehatan Masyarakat Indonesia, 2020)
The underweight still remains a public health problem for toddlers in Indonesia. The purpose of the study to identify the factors related to the underweight incident for toddlers at 24-59 months in urban and rural areas of Indonesia. This research used cross-sectional study design. This study used secondary data on the Total Diet Study-Individual Food Consumption Survey of 2014. The sample size in this study was 5165 toddlers from 24-59 months and distinguished by urban and rural areas. Bivariate Analysis used chi square. This study estimates that 20.3% of children aged 24-59 months were underweight with a greater proportion in rural areas 22.5%. Significant factors related to the underweight incidence in the urban and rural areas were the father's education level (urban; p = 0.02 and rural; p = 0.005) and mother’s education level (urban; p = 0.001 and rural; p = 0.005), number of household members (urban; p = 0.03 and rural; p = 0.012), and energy adequacy level (urban; p = 0.012 and rural; p = 0.005). The factor that was estimated to be significantly related to the underweight incidence just in rural areas as children’s age (p = 0.012), the total number of children in one house (p = 0.047). Multisectoral collaboration is needed to reduce nutritional problems, especially in rural areas. The efforts to improve community nutrition by improving the socio-economic condition of the community should be based on regional capabilities and local wisdom in the region.